2023
DOI: 10.1002/smtd.202201522
|View full text |Cite
|
Sign up to set email alerts
|

High Mobility IZTO Thin‐Film Transistors Based on Spinel Phase Formation at Low Temperature through a Catalytic Chemical Reaction

Abstract: In this paper, In0.22ZnδSn0.78−δO1.89−δ (δ = 0.55) films with a single spinel phase are successfully grown at the low temperature of 300 °C through careful cation composition design and a catalytic chemical reaction. Thin‐film transistors (TFTs) with amorphous In0.22ZnδSn0.78−δO1.89−δ (δ = 0.55) channel layers have a reasonable mobility of 41.0 cm2 V−1 s−1 due to the synergic intercalation of In and Sn ions. In contrast, TFTs with polycrystalline spinel In0.22ZnδSn0.78−δO1.89−δ (δ = 0.55) channel layers, achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…Researchers have explored diverse compositional tuning to extend the application of OSs beyond a -IGZO, aiming to maximize mobility and to improve reliability. 21,22 Beyond IGZO, a variety of OSs with different combinations, including binary oxides (In 2 O 3 , ZnO), 23,24 ternary oxides (IGO, IZO), 25–27 and further combinations like IZTO 28 and IGZTO, 29 has been researched. It is noteworthy that the majority of research and development in the field of OS thin-film transistors (TFTs) has been directed towards their application in flat-panel displays, where the physical channel length tends to be longer, exceeding 1 μm.…”
Section: Emerging Channel Materials and Their Device Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have explored diverse compositional tuning to extend the application of OSs beyond a -IGZO, aiming to maximize mobility and to improve reliability. 21,22 Beyond IGZO, a variety of OSs with different combinations, including binary oxides (In 2 O 3 , ZnO), 23,24 ternary oxides (IGO, IZO), 25–27 and further combinations like IZTO 28 and IGZTO, 29 has been researched. It is noteworthy that the majority of research and development in the field of OS thin-film transistors (TFTs) has been directed towards their application in flat-panel displays, where the physical channel length tends to be longer, exceeding 1 μm.…”
Section: Emerging Channel Materials and Their Device Characteristicsmentioning
confidence: 99%
“…This necessity stems from the comparatively lower mobility of OSs compared to crystalline silicon or TMD. Ongoing efforts to address this limitation involve the composition 34,35 and non-stoichiometry fine-tuning 25,28,36 and thickness scaling, 37,38 as evidenced by the average values presented in the referenced studies (see Table 1). Among various approaches, indium-rich substances such as In 2 O 3 or Sn-doped indium oxide (ITO) emerged as frontrunners in enhancing the on-current of OS FETs, ensuring 20 mA μm −1 in a GAA-structured In 2 O 3 nano-ribbon transistor.…”
Section: Emerging Channel Materials and Their Device Characteristicsmentioning
confidence: 99%
“…Although TFTs are typically prepared at low temperatures, Park et al's research provided initial insights into the mobility and stability of ITZO TFTs after crystallization. Wang et al [60] used a different approach called metal-induced crystallization (MIC) to crystallize ITZO. They coated a 15 nm layer of aluminum (Al) metal on the back-channel surface of the ITZO TFT and annealed it below 400 °C.…”
Section: Post-treatmentmentioning
confidence: 99%
“…To date, numerous studies have been reported to increase the μ FE in oxide TFTs using various approaches such as Sn-doped InGaZnO (IGZO), optimization of the cation composition, crystallization, heterojunctions, dual-gate structures, adjusting channel thickness, and postdeposition annealing (PDA) temperature. , Among them, the crystallization via the PDA is one of the simplest and the most effective approaches to improve the μ FE . However, the crystallization of oxide semiconductors with a ZnO component is generally accomplished at a high temperature (>700 °C) due to its corner-sharing crystal configuration different from In 2 O 3 and Ga 2 O 3 with an edge-sharing configuration crystal structure .…”
Section: Introductionmentioning
confidence: 99%